Informal and formal care in Europe - Tarja K. Viitanen (Institute for the Study of Labor (IZA), 2007)
Government expenditure on formal residential care and home-help services for the elderly significantly reduces 45-59 year old women's informal care-giving affecting both the extensive and the intensive margin. Allowing for country fixed-effects and country-specific trends and correcting for attrition, the estimates - based on the European Community Household Panel - imply that a 1000 Euro increase in the government expenditure on formal residential care and home-help services for the elderly decreases the probability of informal care-giving outside of the caregiver's household by 6 percentage points. Formal care substitutes for informal care that is undertaken outside of the carer's own household, but does not substitute for intergenerational household formation. A simulation exercise shows that an increase in government formal care expenditure is a cost-effective way of increasing the labour force participation rates
urn:nbn:de:101:1-20080416149
Keywords: 330; Pflegedienst; Informeller Sektor; Substitutionseffekt; Pflegeversicherung; EU-Staaten